The Associations between Parity, Family Income, Residence, and Abortion Incidence: A Meta-Analysis - Putri, Annessa Marknalia Sasqia; Soraya, Mira Mashita; Aisy, Jihan Rohadatul; Murti, Bhisma; Munawaroh, Siti Mar'atul (Journal of Maternal and Child Health, 2024)
Background: Abortion is a complex and controversial issue found across the country. The decision to terminate a pregnancy involves many aspects in terms of medical, ethical, moral, religious, social, economic, and legal. Understanding the factors that influence the incidence of abortion is critical to developing strategies to effectively address this issue. This study aims to analyze and estimate the magnitude of the effects of parity, family income, and residence with the incidence of abortion. Subjects and Method: Systematic review and meta-analysis studies were conducted according to the PRISMA flowchart and PICO model. Population: women of childbearing age. Intervention: multipara, high income, and urban residence. Comparison: primapara, low income, and rural residence. Outcome: The incidence of abortion. The basic data used involved Google Scholar, PubMed, BMC, Elsivier, ScienceDirect, and Springer Link. The inclusion criteria are full-text articles with observational study design using multivariate analysis that attaches aOR values and is published from 2014-2023. Data analysis using Review Manager 5.3 application. Results: Ten case control studies and nine cross-sectional studies from the Americas, Africa, and Asia were selected for the meta-analysis. Multiparous (aOR= 1.12; CI 95%= 0.54 to 2.34; p= 0.750), high family income (aOR= 0.55; CI 95%= 0.22 to 1.34; p= 0.190), and urban dwellings (aOR= 1.17; CI 95%= 0.88 to 1.55; p = 0.270) increases the risk of abortion in women of childbearing age, but is not statistically significant. Conclusion: Multipara, high family incomes, and urban residences increase the risk of the likelihood of having an abortion in women of childbearing age, but are not statistically significant.